A novel integrated Model for End‐Stage Liver Disease model predicts short‐term prognosis of hepatitis B virus‐related acute‐on‐chronic liver failure patients. Issue 4 (19th June 2014) - Yan, Huadong; Wu, Wei; Yang, Ying; Wu, Yihua; Yang, Qiao; Shi, Yu
<x xml:space="preserve">Abstract</x> Aim A considerable proportion of chronic hepatitis B (CHB) or hepatitis B virus (HBV)‐related cirrhotic patients develop acute‐on‐chronic liver failure (ACLF) with high short‐term mortality. It remains difficult to accurately predict short‐term prognosis in ACLF patients. The aim of the study is to develop a new prognostic model by assessing new objective variables. Methods A total of 432 HBV‐ACLF patients were recruited into a retrospective observational cohort study including one training and validation cohort. Cox proportional hazard analysis was performed in the training cohort to develop the prognostic model. The performance of the new model was tested in the validation cohort by a receiver–operator curve (ROC). Results During follow up, 241 deaths were reported, with a high 3‐month mortality of 48.4%. On multivariate analysis, age, hepatic encephalopathy (HE) and Model for End‐Stage Liver Disease (MELD) score were found to be significantly associated with 3‐month mortality. The integrated MELD (iMELD) model had a higher area under the ROC than the original MELD, Sequential Organ Failure Assessment (SOFA), Chronic Liver Failure–SOFA and Child–Turcotte–Pugh score (0.853 vs 0.743 vs 0.726 vs 0.764 vs 0.592) in predicting 3‐month mortality. In the validation sample of 212 patients, iMELD remained better than the other models. Conclusion HBV‐ACLF patients are characterized by high short‐term mortality, but steady long‐term survival. A modified MELD model by incorporating age and HE score has better predictive value of 3‐month mortality than other conventional models.